FORMATION OF PRE-SERVICE MATHEMATICS TEACHERS’ COMPUTER MODELING SKILLS IN THE PROCESS OF SOLVING MATH PROBLEMS - Semenikhina , Olena; Drushlyak, Marina (Physical and Mathematical Education, 2022)
Formulation of the problem. The development of information technologies and means has led to the emergence of specialized mathematics software, in which the process of mathematical modeling of various classes of math problems is possible. However, the analysis of scientific and methodological research showed the lack of developed methods of formation of pre-service mathematics teachers’ modeling skills in the process of solving math problems. Materials and methods. Theoretical (theoretical analysis, systematization, and generalization of the results of scientific research to identify the state of the problem, justify its relevance in the training of mathematics teachers; modeling for theoretical justification of methods of formation of pre-service mathematics teachers’ modeling skills in solving math problems), empirical (pedagogical experiment to obtain empirical results of the author's methodology) and statistical (statistical analysis (sign test) to confirm the effectiveness of the developed methodology of formation of pre-service mathematics teachers’ modeling skills in solving math problems).Results. The developed methodology of formation of pre-service mathematics teachers’ modeling skills in solving math problems involves three steps: Step 1 – the teacher offers an example of a visual model of a math problem, and students must independently compose an algorithm for constructing a model; Step 2 – the teacher offers a ready-made algorithm by which students independently reproduce the visual model; Step 3 – students are offered a type of math task (a task for movement, joint work, mixtures, and alloys, etc.), they select the appropriate task and independently construct a visual model.Conclusions. The developed methodology is focused not only on the formation of pre-service teachers’ modeling skills by GeoGebra but also on role-playing in the third stage of its implementation allowing awareness of their own mistakes in future professional activities and typical mistakes of students that are possible in constructing models. Promising scientific research sees the spread of the developed methodology for the training of teachers of natural specialties (biology, chemistry, geography) and testing its effectiveness on the basis of other specialized software.
Keywords: computer simulation; modeling of math problems; methodology of formation of computer modeling skills; pre-service mathematics teachers; professional training; GeoGebra